(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Stabilizing reagents are considered one of the main raw materials for the production of construction materials. Their quality indicators indicate that they provide stability as a stabilizing reagent in a composite mixture in phase. There must be instructions for their production. Taking into account the above, a working manual was proposed to clarify the quality indicators for some of the stabilization reagents. Below is this guideline.